Pengaruh Kecerdasan Emosional dan Motivasi Terhadap Kinerja Pegawai Dinas Kependudukan dan Catatan Sipil Kabupaten Simalungun: Indonesia - Damanik, Lisa Gresti Sella (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
Good public service organizations require quality human resources to improve employee performance. This research was conducted at the Population and Civil Registration Office of Simalungun Regency, which faces problems with employees being less responsive and slow in their work, thus having a negative impact on the government's image in the eyes of the public. The research objective is to determine the influence of emotional intelligence and motivation on employee performance. The research method uses a quantitative approach with data collection through questionnaires to 73 employees as research samples using saturated sampling technique. Data analysis techniques use SPSS 25 program for validity testing, reliability, simple linear regression analysis, correlation coefficient, and coefficient of determination. The research results show that emotional intelligence and motivation have a positive and significant effect on employee performance at the Population and Civil Registration Office of Simalungun Regency. These findings indicate that improving emotional intelligence and work motivation can be an effective strategy to enhance employee performance in public service.